2020
DOI: 10.1038/s41467-020-18622-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional strain dynamics govern the hysteresis in heterogeneous catalysis

Abstract: Understanding catalysts strain dynamic behaviours is crucial for the development of cost-effective, efficient, stable and long-lasting catalysts. Here, we reveal in situ three-dimensional strain evolution of single gold nanocrystals during a catalytic CO oxidation reaction under operando conditions with coherent X-ray diffractive imaging. We report direct observation of anisotropic strain dynamics at the nanoscale, where identically crystallographically-oriented facets are qualitatively differently affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…But note that the strain may propagate from the surface of the crystal into its interior during the reaction as demonstrated in Refs. [40,41] . The large penetration depth of X-rays allows more flexibility on the sample environment; as Bragg coherent X-ray imaging is non-destructive with proper calibration of the X-ray beam attenuation, it can be applied repeatedly during catalytic reaction on the same nanoparticle.…”
Section: Resultsmentioning
confidence: 99%
“…But note that the strain may propagate from the surface of the crystal into its interior during the reaction as demonstrated in Refs. [40,41] . The large penetration depth of X-rays allows more flexibility on the sample environment; as Bragg coherent X-ray imaging is non-destructive with proper calibration of the X-ray beam attenuation, it can be applied repeatedly during catalytic reaction on the same nanoparticle.…”
Section: Resultsmentioning
confidence: 99%
“…Adjusting the reaction temperature can alter the catalytic performance in some cases. Passos et al 203 reported how heating versus cooling cycles influence the single nanoparticle elastic energy landscape. The highly compressive and tensile strain distribution was accordingly changed with temperature and so was the CO oxidation performance.…”
Section: Experimental Operando Applicationmentioning
confidence: 99%
“…In situ Bragg coherent diffraction imaging (BCDI) recently demonstrated the possibility to acquire 3D strain maps of NPs and nanostructures 26 . In particular, the technique has been successfully used to reveal in situ bulk and surface strain dynamics as well as localisation of active sites during reaction 27 29 .…”
Section: Introductionmentioning
confidence: 99%